POLICY INSTRUMENTS FOR THE DEVELOPMENT OF RURAL TOURISM IN THE LEAST DEVELOPED AREAS OF SERBIA: THE EXAMPLE OF THE MUNICIPALITY OF MEDVEĐA - Ljubisavljević, Tijana; Knežević, Miroslav (Economics of Agriculture, 2023)
The paper analyzes the instruments of rural tourism development policy in the least developed areas of the Republic of Serbia on the example of the Municipality of Medveđa. It is based on the hypothesis that economic policy makers, with new legal solutions, have made it possible for agricultural households engaged in rural tourism to apply for IPARD incentives on an equal basis with other agricultural households. Using the semistructured interview technique, research was conducted on the importance of IPARD incentives for the development of rural tourism in the least developed areas of Serbia on the example of the Municipality of Medveđa as well on the significance of the synergistic effect of the development of rural and spa tourism in this local community.